2022
DOI: 10.3390/cancers14112805
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Adrenocortical Carcinoma Relapse and Prognosis with a Set of Novel Multigene Panels

Abstract: Effective assessment of adrenocortical carcinoma (ACC) prognosis is critical in patient management. We report four novel and robust prognostic multigene panels. Sig27var25, SigIQvar8, SigCmbnvar5, and SigCmbn_B predict ACC relapse at area under the curve (AUC) of 0.89, 0.79, 0.78, and 0.80, respectively, and fatality at AUC of 0.91, 0.88, 0.85, and 0.87, respectively. Among their 33 component genes, 31 are novel. They could be differentially expressed in ACCs from normal tissues, tumors with different severity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 98 publications
0
2
0
Order By: Relevance
“…There are a limited number of reports on ACC prognostic biomarkers. Previous studies tried to construct a microarray‐based prognostic predictor and identified genes pair BUB1B and PINK1 as optimal predictors (AUC = 0.83) of poor prognosis in ACC [ 24 , 25 ]. To evaluate the predictive ability of overall status using these 15 genera, we performed area under curve (AUC) receiver operator characteristic (ROC) analysis.…”
Section: Resultsmentioning
confidence: 99%
“…There are a limited number of reports on ACC prognostic biomarkers. Previous studies tried to construct a microarray‐based prognostic predictor and identified genes pair BUB1B and PINK1 as optimal predictors (AUC = 0.83) of poor prognosis in ACC [ 24 , 25 ]. To evaluate the predictive ability of overall status using these 15 genera, we performed area under curve (AUC) receiver operator characteristic (ROC) analysis.…”
Section: Resultsmentioning
confidence: 99%
“…We analyzed Overlap36’s potential in stratification of poor OS of SKCM. We first matched 34 of the 36 murine genes to the human SKCM PanCancer Atlas dataset (for simplicity, these 34 genes are referred to as Overlap36) and merged them into a megagene (Overlap36 risk score) using coefficients generated by multivariate Cox analysis following our system [ 85 , 86 ] as described in Fig. 1 .…”
Section: Resultsmentioning
confidence: 99%